Global, regional, and national burden of NASH related liver cancer in adults aged 45 and above: an analysis from the GBD 2021 and forecast to 2050 - Shi, Jianing; Wu, Xuan; Yu, Jiali; Zhou, Qingli (Frontiers in Nutrition, 2025)
IntroductionNonalcoholic steatohepatitis (NASH) is a more advanced stage of Nonalcoholic fatty liver disease (NAFLD) and is particularly common among middle-aged and older adults. NASH-related liver cancer (NALC) is a serious consequence of NASH progression and has become one of the significant causes of global cancer mortality. However, there is currently no comprehensive analysis of the disease burden in this population. This study aims to comprehensively analyze the incidence of NALC among individuals aged 45 and above worldwide from 1990 to 2021 and to project the trends through 2050.MethodsUsing the data from the Global Burden of Disease 2021, we analyzed incidence, prevalence, mortality, and disability-adjusted life years (DALYs) among adults ≥ 45 from 1990 to 2021, employing frontier risk analysis and Bayesian modeling to project trends through 2050.ResultsIn 2021, among adults aged 45 and above, the age-standardized incidence rate of NALC was 1.69 per 100,000, the prevalence rate was 2.01 per 100,000, the mortality rate was 1.66 per 100,000, and DALYs were 36.69 per 100,000 person-years. Since 1990, global indicators have steadily increased, with low-SDI regions showing the highest incidence, mortality, and DALYs, and high-SDI regions having the highest prevalence. Significant regional and national differences were observed. Future projections suggest that while incidence, mortality, and DALYs will initially rise and then decline, prevalence will continue to increase. By 2050, the age-standardized incidence rate of NALC was projected to reach 1.78 per 100,000, and its age-standardized prevalence rate was projected to reach 2.37 per 100,000 person-years. High fasting blood glucose and metabolic risks were the primary contributors to mortality.ConclusionThese findings suggested the urgent need for developing targeted strategies addressing metabolic-related risk factors and implementing standardized screening protocols to mitigate the growing disease burden of NALC in aging populations.